Matematica per il corso di Economia e Management - Puccetti, Giovanni (Milano University Press, 2023)
This book has been written for the 80-hour course in Mathematics for the Bachelor's Degree in Economics & Management at the University of Milan. The 80 hours are spread over a period of 10 weeks, so each chapter has been designed for one week of the course, with 4 classes of 2 hours each. The book is the outcome of many years of teaching experience at the Polo delle Scienze Sociali, and collects all the notes written by the teacher during the classes, the exercises of the exams, and the several suggestions and corrections sent by the students over the years.